Curbing Inflammation in Multiple Sclerosis and Endometriosis: Should Mast Cells Be Targeted? - David A. Hart (International Journal of Inflammation)
Inflammatory diseases and conditions can arise due to responses to a variety of external and internal stimuli. They can occur acutely in response to some stimuli and then become chronic leading to tissue damage and loss of function. While a number of cell types can be involved, mast cells are often present and can be involved in the acute and chronic processes. Recent studies in porcine and rabbit models have supported the concept of a central role for mast cells in a “nerve-mast cell-myofibroblast axis” in some inflammatory processes leading to fibrogenic outcomes. The current review is focused on the potential of extending aspects of this paradigm into treatments for multiple sclerosis and endometriosis, diseases not usually thought of as having common features, but both are reported to have activation of mast cells involved in their respective disease processes. Based on the discussion, it is proposed that targeting mast cells in these diseases, particularly the early phases, may be a fruitful avenue to control the recurring inflammatory exacerbations of the conditions.